Model Pembelajaran Model Pembelajaran Think Talk Write dan Menulis Karangan Argumentasi pada Era Disrupsi - Susi Alawiyah (Jurnal Inovasi Penelitian, 2021)
The learning model is one of the keys to the success of educators in deliveringlearning material for students. Educators must have the ability to determinelearning models that are in accordance with the conditions of students and learning materials. Conditionin the field shows that many educators do not pay attention to the circumstancesoccurs so that the learning model that is carried out remains. This research aims toknow the effect of the think talk write learning model on the learning outcomes of students inera of disruption. The results showed that the think talk write learning model was capableimprove learning outcomes to write narrative essays at SMK Negeri 5 Tangerang Regency.This learning model is very suitable to be used for the subject of narrative essays in the eradisruption.